MOLLUSCA FAUNA ON CORAL REEFS IN THE WATERS OF CU LAO CHAM ISLANDS (CENTRAL VIETNAM) - Tuyen, Hua Thai (Vietnam Journal of Marine Science and Technology, 2014)
One hundred and two species, in which 73 species of Gastropod and 29 species of Bivalve, belonging to 43 families, 2 classes had been identified through the survey conducted at 15 sites in the waters of Cu Lao Cham islands in 2004 and 2008. Site 8 had the highest composition of species (43 species) following by Sites 3, 4 and 6 (39 species). Site 11 had the least number of species (19 species). Four rare species recorded in Vietnam Red Book included Tridacna squamosa, Tridacna maxima, Pinctada margaritifera, Haliotis ovina. Some commercial species were Turbo chrysostomus, Trochus maculatus, Chicoreus bruneus, Chicoreus torrefastus. The average density of Molluscs in 2008 was 153.76 inds. per 250m2 which was three times higher than that in 2004. Diversity index (H ’), Peilou’s evenness (J’) and similarity index of the species composition among the survey sites depended on the density of both Chama sp. and the unidentified bivalve species.